Axial compressive behaviours of concrete-filled square GFRP tubular columns at low temperatures. (12th December 2022) - Wang, Zhe; Xie, Jian; Wang, Meng-Qin; Yan, Jia-Bao
Highlights: Low temperature greatly increases the ultimate compressive resistance of CFSFTs. GFRP bars exhibit marginal effect on compressive behaviours of CFSFTs. Low temperature improves elastic stiffness of CFSFTs under axial compression. Proposed models predict well low-temperature compression behaviours of CFSFTs. Abstract: This study reported experimental and theoretical investigations on low-temperature compression behaviours of concrete-filled square GFRP tubular (CFSFT) columns. The influences of low temperatures ( T = 20, −30, −60, and −80 °C), thickness of GFRP tubular ( t f = 3.66, 5.26, and 6.49 mm), and spacing of spiral GFRP bars ( S = 40, 60, and 80 mm) on axial compressive behaviours of CFSFT columns were investigated through eighteen axial compression tests. Failure modes, load-axial strain behaviours, dilation behaviours of CFSFT columns, and load–strain behaviours of GFRP bars at low temperatures have been detailed reported. Test results indicated that reducing temperature from 20 to −80 °C decreased the confinement effectiveness of GFRP tubular on concrete core, but improved the compressive strength of GFRP tubular, concrete core and GFRP bars. These improved compressive strengths increased the ultimate compressive capacity of CFSFT columns. Prediction equations have been developed to estimate the ultimate compression capacity and its corresponding axial compression strain of CFSFT columns, which have considered the contribution of longitudinal GFRP bars and spiral GFRP bars. Validations of predictions against test results and comparisons with code predictions proved the improved accuracy of these developed prediction equations.